Perancangan Model Knowledge Management System Pengelolaan Proyek Dengan 10-Step Roadmap Knowledge Management System pada PT. Aegis Ultima Teknologi - Tiawan, Tiawan; Julpikar, Soni; Permana, Budi (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2021)
In the current era of globalization, knowledge is a very valuable asset for companies to increase their effectiveness. Therefore, awareness is needed for companies to foster a culture of sharing knowledge because this will be a valuable asset for the company compared to other assets. To foster a knowledge-sharing culture at PT. Aegis Ultima Teknologi, a knowledge management system is needed, especially in this study using at PT. Aegis Ultima Teknologi the 10-Step Knowledge Management System methodology.